An Ethnographic Case Study on Syrian Children and Their Families in Preschool Class: We are also in this class! - Betül Yanık Özger; Ayşe Akansel (Anı Publishing, 2019)
The aim of this study is to understand the experiences of Syrian children in preschool class and the peer culture they create. The study, which was designed as an ethnographic case study in preschool class. Participantsare 17 children, five year old and their parents. The data were collected in10 months through the participant observer technique and the interview, observation, document analysis. According to the study results, it was understood that the language of speech, the approach of Turkish families and the Turkish children who are popular in the classroom are important elements in peer culture. The teacher's approach towards Syrian children and the teaching materials she used determined the course of the school life. The close relationship of Syrian families with the school and their positive attitudes towards language learning facilitated the children's adaptation to school.